Proyecto de factibilidad para la implementación de una factoría de confecciones de ropa para niños en la ciudad de Quevedo, año 2011 - Rojas García, Diana Beatriz (2012)
This research project is performed market feasibility study, technical, administrative, economic and financial support for the implementation of a garment factory of children`s clothing in the city of Quevedo. As research results of the analysis, the study of market behavior was determined in tastes and preferences of consumers who make up the target market. It also established the projected future demand in five years, and the existence of unmet located in the city of Quevedo, the company considered to cover at least 6% per year, ie 17.280 units of clothing children a year, made its production through the supply of raw materials, supplies, labor machinery and aquipment technology. The technical study identified the optimal location and size of the plant, engineering and technological aspects that make the operation of the factory, and the amount, characteristics and types of machines and equipment needed to produce raised in addition to the requirements operational personnel, administrative, sales. We determined the name, logo, mission, vision, organizational and administrative basis of the project, its main pricing, products, distribution channels, features that served to explain the operation of the company. As in the economic study quantified the necessary investments, the composition of financing, operating costs and sales revenue used for financial evaluation of it. The venture will require an initial investment of $ 39.194,41, intended to finance fixed assets $ 25.808,00 and a working capital of $ 13.386,41, for which 30% of this investment is set by local contribution and 70% funded by the National Development Bank. And finally conducted the study on the financial evaluation to determine the viability or profitability of the factory, the net present value presented a favorable value of $ 53,584.58, the internal rate of return (IRR) of 52% was higher than the rate market interest, a cost-benefit of $ 1.58, to be recoverable within 5 years, by 1 year, 10 months and 16 days. After all, the study concluded that the project is feasible and that the implementation of the factory in the city of Quevedo is possible, its implementation will contribute to the economic recovery of the country fighting the unemployment rate.